2021
DOI: 10.1063/5.0032128
|View full text |Cite
|
Sign up to set email alerts
|

Coherence in single photon emission from droplet epitaxy and Stranski–Krastanov quantum dots in the telecom C-band

Abstract: This is a repository copy of Coherence in single photon emission from droplet epitaxy and Stranski-Krastanov quantum dots in the telecom C-band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
3
43
2
Order By: Relevance
“…DE has been extensively explored by molecular beam epitaxy (MBE) [11][12][13][14] It is only more recently that it has been successfully applied to MOVPE, where promising results have been obtained: for instance, InAs/InP QDs grown via DE in MOVPE have been used in the first entangled quantum lightemitting diode (QLED) emitting in the telecom C-band [15] and in qubit teleportation. [17,19] Our recent study of growth conditions for DE of InAs/InP QDs demonstrated the ability to form QDs in local etched pits, [18] creating the possibility to engineer through the epitaxy process more complex and novel nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…DE has been extensively explored by molecular beam epitaxy (MBE) [11][12][13][14] It is only more recently that it has been successfully applied to MOVPE, where promising results have been obtained: for instance, InAs/InP QDs grown via DE in MOVPE have been used in the first entangled quantum lightemitting diode (QLED) emitting in the telecom C-band [15] and in qubit teleportation. [17,19] Our recent study of growth conditions for DE of InAs/InP QDs demonstrated the ability to form QDs in local etched pits, [18] creating the possibility to engineer through the epitaxy process more complex and novel nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[117] As an alternative, all of the general concepts discussed can also be adapted to different material systems, such as InGaAs QDs, whose emission wavelength can be extended to the telecom C-band. [53,103,[180][181][182] For this purpose, different memory systems for QDs emitting in the telecom C-band are developed. [155,183,184] In conclusion, combining the state-of-the-art QDs with photonic cavities, to maximize the extraction efficiency, and with the well-established tuning techniques, such as electrical or strain tuning to erase FSS and adjust the emission wavelength of the entangled photon pair, all the desirable features for an efficient entangled photon source are at hand: negligible multiphoton emission, [34] high extraction efficiency, [21] degree of entanglement, [20] photonindistinguishability, [35] wavelength-tunability, [72] with on-demand generation [37] .…”
Section: Discussionmentioning
confidence: 99%
“…We find for the BE a T BE of 30 ps and for the DE a T DE of 48 ps. These times are extremely short compared to the radiative lifetime, and the Gaussian shape points towards an efficient spectral diffusion mechanism leading to an inhomogeneous broadening of the QD [40][41][42]. The charge noise can be attributed to the high aluminum content of the AlGaAs waveguide and the impurities in the aluminum source during the sample growth.…”
Section: Coherence Properties Of the Dark Exciton Statementioning
confidence: 99%